Seismic response of intake towers including dam?tower interaction. - Millán, M. A.
The seismic response of the intake?outlet towers has been widely analyzed in recent years. The usual models consider the hydrodynamic effects produced by the surrounding water and the interior water, characterizing the dynamic response of the tower?water?foundation?soil system. As a result of these works, simplified added mass models have been developed. However, in all previous models, the surrounding water is assumed to be of uniform depth and to have infinite extension. Consequently, the considered added mass is associated with only the pressures created by the displacements of the tower itself. For a real system, the intake tower is usually located in proximity to the dam and the dam pressures may influence the equivalent added mass. The objective of this paper is to investigate how the response of the tower is affected by the presence of the dam. A coupled three-dimensional boundary element-finite element model in the frequency domain is employed to analyze the tower?dam?reservoir interaction problem. In all cases, the system response is assumed to be linear, and the effect of the internal fluid and the soil?structure interaction effects are not considered. The results suggest that unexpected resonance amplifications can occur due to changes in the added mass for the tower as a result of the tower?dam?reservoir interaction.
Keywords: CE database subject headings; Intake structures; Seismic analysis; Dams; Hydrodynamic pressures; Fluid?structure interaction; Structural dynamics